Nudging auditors' unconscious to improve performance on an accounting estimate task. Issue 2 (3rd November 2021) - Nolder, Christine J.; Ratzinger‐Sakel, Nicole V. S.; Theis, Jochen C.
Abstract : Auditing deficiencies related to accounting estimates continue to account for a significant percentage of auditing deficiencies identified during routine inspections. Regulators suggest that a lack of auditors' professional skepticism may be to blame. We test a skeptical language priming intervention to induce auditors into a skeptical mindset. Additionally, we posit that skeptical language embedded in a firm's decision aid will induce a skeptical attitude, which we measure in terms of auditors' beliefs and feelings (i.e., confidence and concern) associated with the reasonableness of management's estimate. We find that the skeptical language prime has a positive effect on the quality of auditors' cognitive processing and reasonableness judgments. We also find that the skeptical language keeps auditors' feelings of concern high as opposed to conventional language, which resulted in auditors feeling less concerned. Moreover, we found that auditors' negative feelings of concern were the primary driver of recommended testing both before and after introducing the firm's decision aid.